(untitled) (Journal of Bangladesh Academy of Sciences, 2011)
The effects of three temperature treatments on morphological changes in the apical meristem and contents of GA3 and IAA in leaves during floral bud differentiation in early maturing cultivar of broccoli were studied. Plants went through every stage of flower-bud differentiation at day/night temperatures of 17.3±1/9.3±1°C. At 21.3±1/13.3±1°C, floral bud development ceased after primary axillary scape primordium differentiation and apical meristem entered a reversion stage. The apical meristem remained in the vegetative growth phase in plants growing at 25.3±1/17.3±1°C. Leaf GA3 contents started to increase while IAA contents started to decrease when plants entered the flower bud initiation stage. GA3 content was high and IAA content was low during all stages of axillary scape primordium differentiation. Key words: Meristem development; Broccoli; Apical meristem; GA3; IAA DOI: http://dx.doi.org/10.3329/jbas.v35i1.7966 Journal of Bangladesh Academy of Sciences, Vol.35, No.1, 1-6, 2011